2011
DOI: 10.1177/1367877911419160
|View full text |Cite
|
Sign up to set email alerts
|

‘Mail-order brides’ in popular culture: Colonialist representations and absent discourse

Abstract: Over the past decade clever marketing and wider access to the internet has led to the exponential growth of ‘mail-order’ marriage industries, vastly increasing the number of women who migrate for marriage using these commercial services. Taken within the context of global predatory capitalism, such phenomenon is of interest in that it appears to convene in its dynamics the intersecting operation of gender and class inequality, sexism, racism, and colonialism that, far from diminishing, seems only to further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…A recent study on non-migrants in several European countries explored individual attitudes of non-migrants in exogamous and endogamous unions toward gender equality [ 10 ], and found that non-migrants in mixed unions were more supportive of gender equality than their counterparts in endogamous unions. This finding contradicts the stereotyping that often occurs in the media [ 108 ] or in research on mixed marriages, such as studies on German men who are married to women from Asia [ 66 ] or on German women who are in romantic relationships with men from Sub-Saharan Africa [ 11 ].…”
Section: Employment Patterns Gender Roles and Institutional Influencementioning
confidence: 74%
“…A recent study on non-migrants in several European countries explored individual attitudes of non-migrants in exogamous and endogamous unions toward gender equality [ 10 ], and found that non-migrants in mixed unions were more supportive of gender equality than their counterparts in endogamous unions. This finding contradicts the stereotyping that often occurs in the media [ 108 ] or in research on mixed marriages, such as studies on German men who are married to women from Asia [ 66 ] or on German women who are in romantic relationships with men from Sub-Saharan Africa [ 11 ].…”
Section: Employment Patterns Gender Roles and Institutional Influencementioning
confidence: 74%
“…A very common trope in the show is the question of whether to work out, then the newcomer must go back to their home country. This corresponds to the stereotype that women from non-Western countries are victims that need saving to get out of their home country (Zare and Mendoza, 2012). This, then, positions the American as the saviour.…”
Section: The Other That Needs Saving and The American Saviourmentioning
confidence: 99%
“…They emerged again after the Vietnam War and the closure of US military bases in the Philippines during the 1990s as well as in post‐Cold War Europe (Enloe ). Both the more traditional ‘mail‐order brides’ and the more recent ‘cyber‐brides’ seem to appear where patriarchy and capitalism meet the dynamics of colonisation and post‐colonisation (Zare & Mendoza ).…”
Section: Colonising Eastern Cyberspacementioning
confidence: 99%